Thermal Fatigue Crack Propagation Process and Mechanism of Multicomponent Al-7Si-0.3Mg Alloy - Zhengjun Wang; Xinyang Liu; Chen Dong; Jie Chen; Lianxiang Liu (Crystals, 2023)
The thermal fatigue behavior of multicomponent Al-7Si-0.3Mg alloys in four different treatment states at typical temperature amplitudes 20 °C→350 °C was studied. The morphology of the second phase particles and crack propagation, and distribution characteristics of dislocations in the thermal fatigue specimens of multicomponent Al-7Si-0.3Mg alloys, were analyzed by optical microscopy (OM), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDAX spectrum), and transmission electron microscopy (TEM). The influencing factors, the process, and the mechanism of thermal fatigue crack propagation were mainly studied. The results show that under the same temperature amplitude, the thermal fatigue properties and dislocation densities of the new aluminum alloy and the new aluminum alloy under T6 heat treatment are significantly higher than that of the multicomponent Al-7Si-0.3Mg alloy in cast and refined and modified treatment. The crack growth of thermal fatigue specimen depends on three factors: the temperature amplitude, oxidation, and residual stress. The process of thermal fatigue crack propagation mainly experiences crack initiation and the formation of microcracks, but only a few microcracks continue to expand rapidly or preferentially expand into main cracks. The mechanism of thermal fatigue crack propagation is mainly under the action of thermal stress, the crack tip undergoes a cycle of repeated alternation of sharpening → passivation → sharpening, and the crack continues to move forward from its tip intermittently in the way of propagation → stopping → propagation until fracture failure.